2011
DOI: 10.1007/s00412-011-0356-3
|View full text |Cite
|
Sign up to set email alerts
|

Mutability and mutational spectrum of chromosome transmission fidelity genes

Abstract: It has been more than two decades since the original chromosome transmission fidelity (Ctf) screen of Saccharomyces cerevisiae was published. Since that time the spectrum of mutations known to cause Ctf and, more generally, chromosome instability (CIN) has expanded dramatically as a result of systematic screens across yeast mutant arrays. Here we describe a comprehensive summary of the original Ctf genetic screen and the cloning of the remaining complementation groups as efforts to expand our knowledge of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 78 publications
(115 reference statements)
1
19
0
Order By: Relevance
“…The majority of these genes belong to biological processes, such as DNA repair, previously known to impact mutation rate, and ∼30% of the dMutator genes also cause chromosome instability as seen previously for LOF and ROF mutations (Stirling et al 2012). Incorporating the data from our screen with published data, a total of 210 genes are implicated in increasing the mutator phenotype in yeast (Huang et al 2003; Stirling et al 2012). …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The majority of these genes belong to biological processes, such as DNA repair, previously known to impact mutation rate, and ∼30% of the dMutator genes also cause chromosome instability as seen previously for LOF and ROF mutations (Stirling et al 2012). Incorporating the data from our screen with published data, a total of 210 genes are implicated in increasing the mutator phenotype in yeast (Huang et al 2003; Stirling et al 2012). …”
Section: Discussionmentioning
confidence: 71%
“…The budding yeast Saccharomyces cerevisiae has been a valuable model system for delineating pathways involved in genome instability, and screens in yeast have identified mutator alleles that increase genome instability (Huang et al 2003; Yuen et al 2007; Stirling et al 2012). A forward mutation screen with the nonessential yeast deletion collection identified 33 genes whose null mutations resulted in a mutator phenotype (Huang et al 2003), and 38 essential genes were identified in another screen (Stirling et al 2014).…”
mentioning
confidence: 99%
“…We found that clb5 Δ clb6 Δ most strongly correlated with mutations affecting the establishment of sister-chromatid cohesion, including point mutants in cohesin, smc1-259 , smc3-1 , smc3-42 and in the cohesin loading factor Scc2 ( scc2-4 ) as well as with deletions in CTF4 and CTF18, (Stirling et al, 2012; Yuen et al, 2007) (Figure 6C; Supp. Data 8).…”
Section: Resultsmentioning
confidence: 89%
“…For these reasons, defining genes and pathways that drive CIN and understanding the mechanisms that underlie genome stability will contribute not only to an understanding of tumor etiology and progression but will also be relevant for guiding therapeutic strategies. The budding yeast Saccharomyces cerevisiae has served as an excellent model system for studying highly conserved biological pathways and has been instrumental in delineating pathways involved in genome instability (9). Although the complete spectrum of genes that are mutable to a CIN phenotype [loss-of-function (LOF) and reductionof-function (ROF) alleles] have been determined in yeast (10,11), the spectrum of genes that when amplified or overexpressed cause CIN are less well-defined (12,13).…”
mentioning
confidence: 99%